The reliability of a modified 505 test and change-of-direction deficit time in elite youth football players - Taylor, J. M.; Cunningham, L.; Hood, P.; Thorne, B.; Irvin, G.; Weston, M. (Science and Medicine in Football, 2019)
Change-of-direction ability is an important performance skill in football. Consequently, several testing protocols are used to assess this component. This study assessed the test-retest reliability of a modified 505 test (M505) and the change-of-direction deficit (CODD) in elite youth football players. Data were collected from 110 players from the Under [u] 12-18 years age groups (u18 n = 26, u16 n = 26, u14 n = 39, u12 n = 19) within two English Premier League Category 1 Football Academies. Players completed the M505 twice in 7-days, and a 10-m sprint test for CODD calculation. Reliability was assessed with respect to chronological and biological age (according to PHV status). Typical error (%), minimal detectable change (MDC) (%) and intraclass correlation coefficients (ICCs) were calculated. Typical errors in M505 were moderate to large (2.0-3.2%), while ICCs ranged from low to high (r = 0.26-0.82). Typical errors in CODD were moderate to large (7.1-12.0%), with low to high ICC`s (r = 0.19-0.79). MDC's were 5.5 to 8.9% in M505 and 17.7 to 33.3% in CODD. The typical errors and MDC's observed indicate that the M505 and CODD tests have limited practical utility in elite youth football players.